Challenges in the fabrication of fibre Bragg gratings in silica and polymer microstructured optical fibres. Issue 1 (4th March 2013) - Berghmans, Francis; Geernaert, Thomas; Baghdasaryan, Tigran; Thienpont, Hugo
<x xml:space="preserve">Abstract</x> This paper reviews the state‐of‐the‐art of grating fabrication in silica and polymer microstructured optical fibres. It focuses on the difficulties and challenges encountered during photo‐inscription of such gratings and more specifically on the effect of the air hole lattice microstructure in the cladding of the fibre on the transverse coupling of the coherent writing light to the core region of the fibre. Experimental and computational quantities introduced thus far to assess the influence of the photonic crystal lattice on grating writing efficiency are reviewed as well, together with techniques that have been proposed to mitigate this influence. Finally, early proposals to adapt the microstructure in view of possibly enhancing multi‐photon grating fabrication efficiency are discussed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>